Cuatro reflexiones para meditar sobre el quehacer educativo - Marco Vinicio Vargas-Montero (Universidad Nacional, Costa Rica, 2004)
Education is not limited to the teaching and learning processes; there are many other related topics which often make us meditate. The following are four brief essays that explore different topics; yet, they all deal, in one way or another, with the evaluation process. Among them, the professor's self-assessment through a series of questions, estimating the importance of technology in education, evaluating the teacher while performing his tasks and finally, the appreciation of the public and private university systems. All the topics aim to improve the quality of the different aspects within the area of education, for the benefit of all, especially of those who learn.